2015
DOI: 10.5935/0103-507x.20150026
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist recommendations in an intensive care unit: three-year clinical activities

Abstract: ObjectiveTo analyze the clinical activities performed and the accepted pharmacist recommendations made by a pharmacist as a part of his/her daily routine in an adult clinical intensive care unit over a period of three years.MethodsA cross-sectional, descriptive, and exploratory study was conducted at a tertiary university hospital from June 2010 to May 2013, in which pharmacist recommendations were categorized and analyzed.ResultsA total of 834 pharmacist recommendations (278 per year, on average) were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
2
15
1
3
Order By: Relevance
“…Studies conducted at university hospitals in Fortaleza (CE, Brazil), Curitiba (PR, Brazil), and in the Netherlands, also detected the need for management of dilution and infusion time, dose adjustment and drug withdrawal. ( 1 , 5 , 23 ) Costa, in a study carried out at a university hospital in Campinas (SP, Brazil), showed acceptance of 86.14% of pharmaceutical recommendations made in one year. ( 8 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted at university hospitals in Fortaleza (CE, Brazil), Curitiba (PR, Brazil), and in the Netherlands, also detected the need for management of dilution and infusion time, dose adjustment and drug withdrawal. ( 1 , 5 , 23 ) Costa, in a study carried out at a university hospital in Campinas (SP, Brazil), showed acceptance of 86.14% of pharmaceutical recommendations made in one year. ( 8 )…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown these drugs to be the most frequently responsible for pharmacotherapy-related problems. ( 3 , 5 , 8 , 23 )…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, pharmacotherapy is established as a determining factor in the evolution of these patients. Errors related to medication use are more serious in this sector and are frequently related to fatal outcomes and/or requiring additional life support measures [3][4][5] .…”
Section: Rbfhss Revista Brasileira De Farmácia Hospitalar E Serviços mentioning
confidence: 99%
“…Merali et al, made many recommendations to reduce drug medication errors at different stages .Recommendations to reduce medication errors. Many organizations are now dedicated to patient safety" [18].…”
Section: These Are As Followsmentioning
confidence: 99%
“…This inding might be due to improvement of the clinical knowledge of the pharmacist and his/her more thorough integration with the ICU multi-professional staff. According to the BIOMEDICAL literature, pharmacist's actions in the ICU should not to be limited to providing advice to the equip but also include pro-active participation in decision-making in the maintenance of pharmacological treatment" [18].…”
Section: These Are As Followsmentioning
confidence: 99%